ELECTRICITY STORAGE ELEMENT, METHOD FOR PRODUCING ELECTRICITY STORAGE ELEMENT, AND ELECTRICITY STORAGE DEVICE
The wound electrode body design with horizontal axis and controlled electrolyte distribution addresses electrolyte depletion in hollow active material particles, maintaining low resistance and high output in power storage elements.
Patent Information
- Application Number
- JP2022509944
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-23
- Filing Date
- 2021-03-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-03-15
AI Technical Summary
Hollow active material particles in power storage elements are prone to deformation during charging and discharging, leading to increased resistance and decreased output due to electrolyte depletion and capillary penetration issues, especially in wound-type electrode bodies.
A wound electrode body design with hollow active material particles, where the winding axis is parallel to the horizontal direction, and the central portion is pressed, ensuring a surplus electrolyte is present between the electrode body and the container, with specific width-to-height ratios for the active material layers and separator, facilitating uniform electrolyte distribution.
The design maintains low resistance and high output performance even after charge/discharge cycles by ensuring uniform electrolyte penetration and minimizing depletion, thereby reducing resistance and maintaining energy density.
Smart Images

Figure 0007616210000002 
Figure 0007616210000003 
Figure 0007616210000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an energy storage element, a manufacturing method for an energy storage element, and an energy storage device. [Background technology]
[0002] Chargeable and dischargeable electricity storage elements (secondary batteries, capacitors, etc.) are used in various devices such as electric vehicles and other vehicles and home appliances. Known electricity storage elements include those equipped with a wound electrode body in which a strip-shaped positive electrode and a strip-shaped negative electrode are wound in a superimposed state with a strip-shaped separator interposed therebetween. Such an electrode body is housed in a container together with an electrolyte to form an electricity storage element.
[0003] One method for increasing the output of an electricity storage element is known to be the use of hollow active material particles in the positive or negative electrode (see Patent Documents 1 and 2). In the case of hollow active material particles, the electrolyte penetrates into the hollow spaces inside the particles, increasing the contact area between the active material particles and the electrolyte, lowering the resistance and increasing the output. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 8-321300 [Patent Document 2] JP 2011-119092 A Summary of the Invention [Problem to be solved by the invention]
[0005] The hollow active material particles as described above have a weak strength due to their hollow structure. Therefore, the hollow active material particles are easily deformed with repeated charging and discharging, which tends to result in a decrease in the output of the storage element. Specifically, if the hollow active material particles expand during charging, they are difficult to return to their original state even when discharged, causing a decrease in the conductivity between the particles. Therefore, in order to suppress the expansion of the hollow active material particles during charging, it has been considered to use the storage element in a state in which the electrode body is pressed from the outside. When the electrode body is used in this pressed state, the hollow active material particles are deformed so that the hollow portion becomes smaller during charging due to the suppression of the expansion of the hollow active material particles. Therefore, the electrolyte in the hollow portion is pushed out and flows out of the electrode body. Then, during discharging, the hollow active material particles return to their original shape, and the electrolyte flows into the hollow portion of the particle. The inflow of the electrolyte into the electrode body is due to the capillary phenomenon, and it may take several minutes to several hours for the electrolyte to completely penetrate into the electrode body to its original state, depending on the design of the strength of the pressure applied to the electrode body. For this reason, when charging and discharging are frequently repeated, or when discharging is performed rapidly, the electrolyte may not penetrate into the electrode body at the time of discharge and the electrolyte may run out in some places in the electrode body. In particular, in the case of a wound electrode body, the electrolyte can only penetrate from both end faces of the electrode body, so the electrolyte is likely to run out in the center of the electrode body. In addition, the electrode body is usually pressed from the center, so the electrolyte is likely to run out in the center of the electrode body. When the electrolyte in the electrode body is partially exhausted in this way, the resistance increases and the output decreases. In addition, when charging and discharging are repeated in a state where the electrolyte in the electrode body is exhausted, the deterioration of the storage element is accelerated and the resistance increases.
[0006] The present invention has been made based on the above-mentioned circumstances, and its object is to provide an energy storage element having a wound-type electrode body and having low resistance even after charge-discharge cycles, a manufacturing method thereof, and an energy storage device including such an energy storage element. [Means for solving the problem]
[0007] One aspect of the present invention is an energy storage element (A) comprising: an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in the longitudinal direction; an electrolyte; and a container for accommodating the electrode body and the electrolyte; at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles; a winding axis of the electrode body is arranged parallel to the horizontal direction; the container is compressed such that at least a central portion of the electrode body is in a pressed state; excess electrolyte, which is a part of the electrolyte, is present between the electrode body and the container; a lower end of the electrode body is in contact with the excess electrolyte; and a relationship between a height H from a liquid level of the excess electrolyte to an upper end of the electrode body and a width Wc of the positive electrode active material layer satisfies the following formula 1. 0.8H≦Wc≦2.0H 1
[0008] Another aspect of the present invention is a storage element (B) comprising: an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in the longitudinal direction; an electrolyte; and a container for accommodating the electrode body and the electrolyte; at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles; a winding axis of the electrode body is arranged parallel to the horizontal direction; the container is compressed such that at least a central portion of the electrode body is in a pressed state; excess electrolyte, which is a part of the electrolyte, is present between the electrode body and the container; a lower end of the electrode body is in contact with the excess electrolyte; and a relationship between a height H from a liquid level of the excess electrolyte to an upper end of the electrode body and a width Wa of the negative electrode active material layer satisfies the following formula 2. 0.9H≦Wa≦2.1H 2
[0009] Another aspect of the present invention is an energy storage element (C) comprising: an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in the longitudinal direction; an electrolyte; and a container for accommodating the electrode body and the electrolyte, wherein at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles, the winding axis of the electrode body is arranged parallel to the horizontal direction, the container is compressed such that at least a central portion of the electrode body is in a pressed state, excess electrolyte that is a part of the electrolyte is present between the electrode body and the container, a lower end of the electrode body is in contact with the excess electrolyte, and a relationship between a height H from a liquid level of the excess electrolyte to an upper end of the electrode body and a width Ws of the separator satisfies the following formula 3. 1.0H≦Ws≦2.2H 3
[0010] Another aspect of the present invention is a method for producing an energy storage element, comprising: housing an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a strip-shaped negative electrode active material layer, and a strip-shaped separator in a longitudinal direction, and an electrolyte in a container; and compressing the container, wherein at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles; in the housing, a winding axis of the electrode body is arranged parallel to the horizontal direction; by compressing, at least a central portion of the electrode body is pressed; an excess electrolyte that is a part of the electrolyte is present between the electrode body and the container; a lower end of the electrode body is in contact with the excess electrolyte; and, when a height from a liquid level of the excess electrolyte to an upper end of the electrode body is H, a width of the positive electrode active material layer is Wc, a width of the negative electrode active material layer is Wa, and a width of the separator is Ws, at least one of the following formulas 1 to 3 is satisfied: 0.8H≦Wc≦2.0H 1 0.9H≦Wa≦2.1H 2 1.0H≦Ws≦2.2H 3
[0011] Another embodiment of the present invention is an energy storage device including one or more energy storage elements, at least one of which is the energy storage element (A), the energy storage element (B), or the energy storage element (C). Effect of the Invention
[0012] According to one embodiment of the present invention, it is possible to provide an energy storage element including a wound electrode body and having low resistance even after charge / discharge cycles, a manufacturing method thereof, and an energy storage device including such an energy storage element. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic perspective view showing an energy storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic perspective view showing components disposed in a container of the energy storage device of FIG. [Diagram 3] FIG. 3 is a schematic perspective view showing the outline of the configuration of an electrode body of the energy storage element of FIG. [Figure 4] FIG. 4 is a schematic cross-sectional view of the energy storage element of FIG. [Diagram 5] FIG. 5 is a schematic diagram showing the relationship between the electrode body and excess electrolyte of the electricity storage element of FIG. [Figure 6] 6 is a schematic partial cross-sectional view of an electrode body of the energy storage element of FIG. [Figure 7] FIG. 7 is a schematic plan view showing an electricity storage device formed by assembling a plurality of the electricity storage elements of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] First, an overview of the energy storage element, the manufacturing method thereof, and the energy storage device disclosed in this specification will be described.
[0015] An energy storage element according to one aspect of the present invention includes an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in the longitudinal direction, an electrolyte, and a container for accommodating the electrode body and the electrolyte, wherein at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles, the winding axis of the electrode body is arranged parallel to the horizontal direction, the container is compressed such that at least a central portion of the electrode body is in a pressed state, excess electrolyte that is a part of the electrolyte is present between the electrode body and the container, a lower end of the electrode body is in contact with the excess electrolyte, and the relationship between a height H from a liquid level of the excess electrolyte to an upper end of the electrode body and a width Wc of the positive electrode active material layer satisfies the following formula 1. 0.8H≦Wc≦2.0H 1
[0016] The electric storage element (A) is an electric storage element having a wound electrode body, and has low resistance even after charge / discharge cycles. The reason why such an effect occurs is not clear, but the following reason is presumed. In an electric storage element having a wound electrode body in which the winding axis is arranged parallel to the horizontal direction, the excess electrolyte in the container penetrates into the electrode body from the lower end parts of both end faces of the electrode body during discharge (see FIG. 5, etc.). When the width of the electrode body, specifically the width Wc of the positive electrode active material layer, is relatively too wide, the electrolyte does not easily penetrate to the center of the electrode body, and a portion where the electrolyte is depleted is likely to occur. On the other hand, when the width Wc of the positive electrode active material layer is relatively too narrow, the opposing area between the positive electrode active material layer and the negative electrode active material layer becomes small, so that the current density during charge / discharge increases and the initial resistance increases. In contrast, in the energy storage element (A), the width Wc of the positive electrode active material layer is within a predetermined range relative to the height H from the liquid level of the excess electrolyte to the upper end of the electrode body, so that the electrolyte can easily and uniformly permeate the entire electrode body, making it difficult for parts to become depleted of electrolyte, and the initial resistance is also sufficiently low. For this reason, it is presumed that the resistance of the energy storage element (A) remains low even after charge-discharge cycles.
[0017] The height of the liquid level of the excess electrolyte is based on the position of the liquid level in a discharged state. The discharged state refers to a state in which the storage element is discharged at a constant current of 0.2 C up to the discharge end voltage. The discharge end voltage may be the lowest discharge voltage at which discharge can be practically performed, and may be a value determined by the settings of the electrical device using the storage element. The discharge end voltage may be, for example, 2.5 V. For example, in the case of a non-aqueous electrolyte storage element in which the positive electrode active material is a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure or a spinel type crystal structure, and the negative electrode active material is a carbon material (graphite, non-graphitic carbon, etc.), the discharge end voltage may be 2.5 V. In addition, after the constant current discharge, the position of the liquid level is measured after leaving it for one hour or more.
[0018] Moreover, hollow active material particles refer to active material particles having a hollow portion (void) inside the particle. Specifically, hollow means that in the cross section of the particle observed in an SEM image obtained using a scanning electron microscope (SEM), the area ratio R excluding the voids in the particle to the entire particle area is less than 95%. The area ratio R of the hollow active material particles may be 50% or more and 95% or less, or 60% or more and 90% or less. The area ratio R can be determined as follows. (1) Preparation of the measurement sample The active material particles to be measured are fixed with a thermosetting resin. A cross-section polisher is used to expose the cross section of the active material particles fixed with the resin, and a measurement sample is prepared. (2) Obtaining SEM (scanning electron microscope) images To obtain SEM images, a scanning electron microscope JSM-7001F (manufactured by JEOL Ltd.) is used. SEM images are obtained by observing secondary electron images. The acceleration voltage is 15 kV. The observation magnification is set so that 3 to 15 active material particles appear in one field of view. The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the contours of the active material particles are clearly visible. (3) Cutting out the outline of active material particles The image cutting function of the image editing software Adobe Photoshop Elements 11 is used to cut out the outlines of the active material particles from the acquired SEM image. This cutting out of the outlines is performed by using the quick selection tool to select the area outside the outlines of the active material particles, and editing everything other than the active material particles to a black background. If the outlines of less than three active material particles were successfully cut out at this time, another SEM image is acquired and the process is repeated until the outlines of three or more active material particles are successfully cut out. (4) Binarization The image of the first active material particle among the cut out active material particles is binarized using the image analysis software PopImaging 6.00, with a concentration 20% lower than the concentration at which the intensity is at its maximum set as the threshold. The area of the lower concentration side is calculated by the binarization process to obtain the "area S1 excluding voids in the particle". Next, the same image of the first active material particle as above is binarized with a concentration of 10 as the threshold. The outer edge of the active material particle is determined by the binarization process, and the area inside the outer edge is calculated to obtain the "area S0 of the entire particle". The ratio of S1 to S0 (S1 / S0) is calculated using the calculated S1 and S0, to obtain the "area ratio R1 (=S1 / S0) of the entire particle area excluding voids in the particle" for the first active material particle. The images of the second and subsequent active material particles among the cut out active material particles are also binarized as described above to calculate the areas S1 and S0. Based on the calculated areas S1 and S0, the area ratios R2, R3, . . . of each active material particle are calculated. (5) Determination of area ratio R The "area ratio R of the active material particles excluding voids within the particles to the area of the entire particles" is determined by calculating the average value of all the area ratios R1, R2, R3, ... calculated by the binarization process.
[0019] According to another aspect of the present invention, there is provided an energy storage element (B) including: an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in the longitudinal direction; an electrolyte; and a container for accommodating the electrode body and the electrolyte; at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles; a winding axis of the electrode body is arranged parallel to the horizontal direction; the container is compressed such that at least a central portion of the electrode body is in a pressed state; excess electrolyte, which is a part of the electrolyte, is present between the electrode body and the container; a lower end of the electrode body is in contact with the excess electrolyte; and the relationship between a height H from a liquid level of the excess electrolyte to an upper end of the electrode body and a width Wa of the negative electrode active material layer satisfies the following formula 2. 0.9H≦Wa≦2.1H 2
[0020] The storage element (B) is also an energy storage element having a wound electrode body, and has low resistance even after charge / discharge cycles. Although the reason why such an effect occurs is unclear, it is presumed to be due to the same reason as the storage element (A) described above, that is, the width Wa of the negative electrode active material layer is within a predetermined range with respect to the height H from the liquid level of the excess electrolyte to the upper end of the electrode body, so that the electrolyte can easily permeate the entire electrode body with high uniformity, making it difficult for parts to run out of electrolyte, and also making the initial resistance sufficiently low.
[0021] According to another aspect of the present invention, there is provided an energy storage element (C) including: an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in the longitudinal direction; an electrolyte; and a container for accommodating the electrode body and the electrolyte; at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles; a winding axis of the electrode body is arranged parallel to the horizontal direction; the container is compressed such that at least a central portion of the electrode body is in a pressed state; excess electrolyte, which is a part of the electrolyte, is present between the electrode body and the container; a lower end of the electrode body is in contact with the excess electrolyte; and the relationship between a height H from a liquid level of the excess electrolyte to an upper end of the electrode body and a width Ws of the separator satisfies the following formula 3. 1.0H≦Ws≦2.2H 3
[0022] The electric storage element (C) is also an electric storage element having a wound electrode assembly, and has low resistance even after charge / discharge cycles. The reason why such an effect occurs is not clear, but it is assumed to be due to the same reason as the electric storage element (A) described above, that is, the width Ws of the separator is within a predetermined range with respect to the height H from the liquid level of the excess electrolyte to the upper end of the electrode assembly, so that the electrolyte can easily permeate the entire electrode assembly with high uniformity, making it difficult for parts to become depleted of the electrolyte, and also making the initial resistance sufficiently low.
[0023] In the electric storage element (A), the electric storage element (B), and the electric storage element (C), it is preferable that the relationship between the average thickness Tc of the positive electrode active material layer, the average thickness Ta of the negative electrode active material layer, and the average thickness Ts of the separator, and the height H, satisfies the following formula 4. 1.0H≦500(Tc+Ta+Ts)≦2.0H 4
[0024] In such a case, the resistance of the energy storage element after the charge-discharge cycle is lower. Although the reason for this is unclear, it is speculated that by adjusting the total thickness of the positive electrode active material layer, the negative electrode active material layer, and the separator, which are porous and through which the electrolyte solution permeates, the permeation speed of the electrolyte solution in the height direction due to the capillary phenomenon is optimized, and when the relationship satisfies the above formula 4, the electrolyte solution can sufficiently permeate up to the upper end part of the electrode body.
[0025] The average thickness Tc of the positive electrode active material layer is the average thickness of one or more positive electrode active material layers provided on one positive electrode. For example, when two positive electrode active material layers are provided on the positive electrode, it is the average thickness of the two positive electrode active material layers. For example, when the positive electrode has a structure in which a positive electrode active material layer is provided on both sides of the positive electrode substrate, the average thickness Tc of the positive electrode active material layer is the average thickness of the positive electrode substrate minus the average thickness of the positive electrode substrate. The same applies to the average thickness Ta of the negative electrode active material layer. In addition, the average thickness Tc of the positive electrode active material layer, the average thickness Ta of the negative electrode active material layer, and the average thickness Ts of the separator are each the average of the thickness measurements at any five points.
[0026] A method for producing an electric storage element according to one aspect of the present invention includes: housing an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in a longitudinal direction, and an electrolyte in a container; and compressing the container, wherein at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles; in the housing, a winding axis of the electrode body is arranged parallel to the horizontal direction; by compressing, at least a central portion of the electrode body is pressed; an excess electrolyte that is a part of the electrolyte is present between the electrode body and the container; a lower end of the electrode body is in contact with the excess electrolyte; and when a height from a liquid level of the excess electrolyte to an upper end of the electrode body is H, a width of the positive electrode active material layer is Wc, a width of the negative electrode active material layer is Wa, and a width of the separator is Ws, at least one of the following formulas 1 to 3 is satisfied: 0.8H≦Wc≦2.0H 1 0.9H≦Wa≦2.1H 2 1.0H≦Ws≦2.2H 3
[0027] According to this manufacturing method, it is possible to manufacture an energy storage element that includes a wound electrode body and has low resistance even after charge / discharge cycles.
[0028] A power storage device according to one embodiment of the present invention includes one or more power storage elements, at least one of which is the power storage element (A), the power storage element (B), or the power storage element (C).
[0029] The electricity storage device is an electricity storage device including an electricity storage element having a wound electrode body, and has low resistance even after charge / discharge cycles.
[0030] An energy storage element, a manufacturing method for an energy storage element, and an energy storage device according to one embodiment of the present invention will be described in detail below.
[0031] <Electricity storage element> Fig. 1 is a perspective view showing the appearance of an energy storage device 10 according to one embodiment of the present invention. Fig. 2 is a perspective view showing components arranged in a container of the energy storage device 10. Note that the dashed dotted line marked with the symbol W in Fig. 2 represents the winding axis of the electrode body 16. The winding axis W is an imaginary axis, and in this embodiment, is a straight line parallel to the Y axis.
[0032] As shown in Fig. 1, the energy storage element 10 includes a container 11, a positive electrode terminal 12, and a negative electrode terminal 13. As shown in Fig. 2, the energy storage element 10 includes a positive electrode current collector 14, a negative electrode current collector 15, and an electrode body 16, which are contained in the container 11 (container body 17). Furthermore, the energy storage element 10 includes an electrolyte (not shown in Fig. 2) contained in the container 11.
[0033] The container 11 is composed of a container body 17 having a rectangular cylindrical shape and a bottom, and a lid body 18 which is a plate-like member that closes the opening of the container body 17. The container 11 is usually made of metal or resin. The container 11 has a structure in which the electrode body 16 and the like are accommodated inside, and then the lid body 18 and the container body 17 are welded together, for example, to seal the inside. After the inside is sealed, the wall surfaces 19 of the container 11 (a pair of wall surfaces 19 with the X-axis direction as the normal direction) are compressed and have an inwardly recessed shape. As the container 11 is compressed in this manner, at least the center of the electrode body 16 is pressed.
[0034] The positive electrode terminal 12 is an electrode terminal electrically connected to the positive electrode of the electrode body 16 via a positive electrode current collector 14. The negative electrode terminal 13 is an electrode terminal electrically connected to the negative electrode of the electrode body 16 via a negative electrode current collector 15. The positive electrode terminal 12 and the negative electrode terminal 13 are attached to a lid 18 disposed above the electrode body 16 via an insulating gasket (not shown).
[0035] The positive electrode current collector 14 is a conductive member that electrically connects the positive electrode terminal 12 and the positive electrode of the electrode body 16. The negative electrode current collector 15 is a conductive member that electrically connects the negative electrode terminal 13 and the negative electrode of the electrode body 16. The positive electrode current collector 14 and the negative electrode current collector 15 are fixed to a lid 18. In addition, the positive electrode current collector 14 is joined to the positive electrode end of the electrode body 16, and the negative electrode current collector 15 is joined to the negative electrode end of the electrode body 16.
[0036] The electrode body 16 is a flat, wound electrode body. As shown in Fig. 3, the electrode body 16 is formed by winding a strip-shaped positive electrode 21, a strip-shaped first separator 22a, a strip-shaped negative electrode 23, and a strip-shaped second separator 22b in a stacked state in this order in the longitudinal direction. The electrode body 16 is disposed such that its winding axis W is parallel to the horizontal direction (Y-axis). In the energy storage element 10, the winding axis W of the electrode body 16 is parallel to the bottom surface of the container 11.
[0037] As shown in Figs. 3 and 6, the positive electrode 21 has a strip-shaped positive electrode substrate 25 and a positive electrode active material layer 26 laminated on both sides of the positive electrode substrate 25. The negative electrode 23 has a strip-shaped negative electrode substrate 27 and a negative electrode active material layer 28 laminated on both sides of the negative electrode substrate 27. The positive electrode substrate 25 and the negative electrode substrate 27 are conductive substrates such as metal foils. At least one of the positive electrode active material layer 26 and the negative electrode active material layer 28 has hollow active material particles. It is preferable that both the positive electrode active material layer 26 and the negative electrode active material layer 28 have hollow active material particles. Details of each component will be described later.
[0038] In the electrode body 16, the positive electrode 21 and the negative electrode 23 are wound with a mutual shift in the direction of the winding axis W via the separator 22 (22a, 22b). Specifically, the positive electrode 21 has a positive electrode active material layer non-laminated portion 29 where the positive electrode active material layer 26 is not laminated at one end in the direction of the winding axis W (the end on the negative side in the Y-axis direction in FIG. 3). The negative electrode 23 has a negative electrode active material layer non-laminated portion 30 where the negative electrode active material layer 28 is not laminated at the other end in the direction of the winding axis W (the end on the positive side in the Y-axis direction in FIG. 3). In this way, the positive electrode side end is formed by the exposed positive electrode substrate 25 (positive electrode active material layer non-laminated portion 29), and the negative electrode side end is formed by the exposed negative electrode substrate 27 (negative electrode active material layer non-laminated portion 30). The positive electrode side end is joined to the positive electrode current collector 14, and the negative electrode side end is joined to the negative electrode current collector 15.
[0039] In such a flat, wound electrode body 16, pressure is usually applied from the center of the flat portion. That is, the center of the electrode body 16 as viewed in the X-axis direction is usually subjected to the greatest load.
[0040] As described above, the container 11 further contains an electrolyte. The electrolyte is impregnated into the porous positive electrode active material layer 26, the negative electrode active material layer 28, and the separator 22, and a part of the electrolyte is stored at the bottom of the container 11 as excess electrolyte 31. That is, as shown in FIG. 4, the excess electrolyte 31 exists between the electrode body 16 and the container 11. At least the lower end of the electrode body 16 is in contact with the excess electrolyte 31. It is preferable that the lower end of the electrode body 16 is immersed in the excess electrolyte 31. For example, it is more preferable that at least half of the lower curved portion 16A (semicircular portion in cross-sectional view) of the electrode body 16, preferably substantially the entire lower curved portion 16A of the electrode body 16, is immersed in the excess electrolyte 31.
[0041] In one embodiment of the energy storage element 10, the relationship between the height H from the liquid level of the excess electrolyte 31 to the upper end of the electrode body 16 and the width Wc of the positive electrode active material layer 26 satisfies the following formula 1 (see FIGS. 5 and 6). 0.8H≦Wc≦2.0H 1
[0042] The lower limit of Wc is preferably 1.0H, more preferably 1.2H, even more preferably 1.4H, even more preferably 1.6H, and particularly preferably 1.8H. The upper limit of Wc is preferably 1.9H. By setting Wc to the above lower limit or more, the electrolyte can sufficiently penetrate to the upper end of the electrode body 16, so that the initial resistance can be reduced. In addition, the volume ratio of the positive electrode active material layer 26 to the volume of the energy storage element 10 can be sufficiently increased, so that the energy density per volume of the energy storage element can be increased. On the other hand, by setting Wc to the above upper limit or less, the electrolyte can sufficiently penetrate to the center of the electrode body 16. Therefore, in the energy storage element 10, when Wc is in the above range, the resistance is low even after the charge / discharge cycle.
[0043] In one aspect of the energy storage element 10, the relationship between the height H from the liquid level of the excess electrolyte 31 to the upper end of the electrode body 16 and the width Wa of the negative electrode active material layer 28 satisfies the following formula 2 (see FIGS. 5 and 6). 0.9H≦Wa≦2.1H 2
[0044] The lower limit of Wa is preferably 1.0H, more preferably 1.2H, even more preferably 1.4H, even more preferably 1.6H, and particularly preferably 1.8H. The upper limit of Wa is preferably 2.0H. By setting Wa to the above lower limit or more, the electrolyte can sufficiently penetrate to the upper end of the electrode body 16, so that the initial resistance can be reduced. In addition, the volume ratio of the negative electrode active material layer 28 to the volume of the energy storage element 10 can be sufficiently increased, so that the energy density per volume of the energy storage element can be increased. On the other hand, by setting Wa to the above upper limit or less, the electrolyte can sufficiently penetrate to the center of the electrode body 16. Therefore, in the energy storage element 10, when Wa is in the above range, the resistance is low even after the charge / discharge cycle.
[0045] In one aspect of the energy storage element 10, the relationship between the height H from the liquid level of the excess electrolyte 31 to the upper end of the electrode assembly 16 and the width Ws of the separator 22 satisfies the following formula 3 (see FIGS. 5 and 6). 1.0H≦Ws≦2.2H 3
[0046] The lower limit of Ws is preferably 1.2H, more preferably 1.4H, even more preferably 1.6H, even more preferably 1.8H, and particularly preferably 1.9H. The upper limit of Ws is preferably 2.0H. By setting Ws to the above lower limit or more, the electrolyte can sufficiently penetrate to the upper end of the electrode body 16. In addition, the width of the positive electrode active material layer 26 and the negative electrode active material layer 28 is generally narrower than the width of the separator 22. Therefore, by making the width of the separator 22 sufficiently wide, the width of the positive electrode active material layer 26 and the negative electrode active material layer 28 can be widened, and the volume ratio of the positive electrode active material layer 26 and the negative electrode active material layer 28 to the volume of the storage element 10 can be sufficiently increased, so that the energy density per volume of the storage element can be increased. On the other hand, by setting Ws to the above upper limit or less, the electrolyte can sufficiently penetrate to the center of the electrode body 16. Therefore, in the storage element 10, when Ws is in the above range, the resistance is low even after the charge / discharge cycle.
[0047] In one embodiment of the energy storage element 10, when the height from the liquid level of the excess electrolyte 31 to the upper end of the electrode body 16 is H, the width of the positive electrode active material layer 26 is Wc, the width of the negative electrode active material layer 28 is Wa, and the width of the separator 22 is Ws, at least one of the following formulas 1 to 3 is satisfied. 0.8H≦Wc≦2.0H 1 0.9H≦Wa≦2.1H 2 1.0H≦Ws≦2.2H 3 The preferred ranges of Wc, Wa, and Ws are the same as those described above.
[0048] The height H from the liquid level of the excess electrolyte 31 to the upper end of the electrode body 16 may be, for example, 30 mm or more and 150 mm or less, or 40 mm or more and 120 mm or less.
[0049] It is preferable that the relationship between the average thickness Tc of the positive electrode active material layer 26, the average thickness Ta of the negative electrode active material layer 28, and the average thickness Ts of the separator 22 and the height H satisfies the following formula 4. 1.0H≦500(Tc+Ta+Ts)≦2.0H 4
[0050] The lower limit of 500(Tc+Ta+Ts) is more preferably 1.2H, and even more preferably 1.4H. The upper limit of 500(Tc+Ta+Ts) is more preferably 1.8H, and even more preferably 1.6H. By setting the value of 500(Tc+Ta+Ts) within the above range, the electrolyte can sufficiently penetrate to the upper end portion of the electrode body 16, and the resistance after the charge-discharge cycles is lowered.
[0051] The average thickness Tc of the positive electrode active material layer 26 may be, for example, 10 μm or more and 200 μm or less, or 20 μm or more and 100 μm or less. The average thickness Ta of the negative electrode active material layer 28 may be, for example, 10 μm or more and 200 μm or less, or 20 μm or more and 120 μm or less. The average thickness Ts of the separator 22 may be, for example, 5 μm or more and 100 μm or less, or 10 μm or more and 40 μm or less.
[0052] In addition, it is preferable that the relationship between the average thickness Tp of the porous portion between the positive electrode substrate 25 and the negative electrode substrate 27 and the height H satisfies the following formula 5. 1.1H≦1000Tp≦2.2H 5
[0053] The lower limit of 1000Tp is more preferably 1.2H, further preferably 1.4H, and even more preferably 1.6H. The upper limit of 1000Tp is more preferably 2.0H, and even more preferably 1.9H. By setting the value of 1000Tp within the above range, the electrolyte can sufficiently penetrate to the upper end portion of the electrode body 16, and the resistance after the charge-discharge cycle is lowered.
[0054] In the energy storage element 10 according to this embodiment shown in FIG. 6 etc., the average thickness Tp is the sum of the average thickness of one layer of the positive electrode active material layer 26, the average thickness of one layer of the negative electrode active material layer 28, and the average thickness of the separator 22. The average thickness of one layer of the positive electrode active material layer 26 may be, for example, 5 μm or more and 100 μm or less, or 10 μm or more and 50 μm or less. The average thickness of one layer of the negative electrode active material layer 28 may be, for example, 5 μm or more and 100 μm or less, or 10 μm or more and 60 μm or less.
[0055] The energy storage element according to one embodiment of the present invention can be suitably used in applications where the electrolyte cannot keep up with the permeation into the electrode body during discharge, such as when charging and discharging are frequently repeated or when discharging is rapidly performed, etc. Such applications include a power source for vehicles, and in particular, the energy storage element can be suitably used as a power source for vehicles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs).
[0056] Hereinafter, main components of an energy storage device according to one embodiment of the present invention will be described in detail.
[0057] (positive electrode) As described above, the positive electrode 21 has a positive electrode substrate and a positive electrode active material layer laminated on both sides of the positive electrode substrate. The positive electrode may further have an intermediate layer provided between the positive electrode substrate and the positive electrode active material layer. Also, a positive electrode in which a positive electrode active material layer is laminated on only one side of the positive electrode substrate may be used.
[0058] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).
[0059] The positive electrode substrate may be a plate or sheet having a substantially uniform thickness. The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased while increasing the energy density per volume of the storage element. The "average thickness" of the positive electrode substrate and the negative electrode substrate described later refers to the value obtained by dividing the punched mass when a substrate having a predetermined area is punched out by the true density and punched area of the substrate.
[0060] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.
[0061] The positive electrode active material layer contains a positive electrode active material and, as necessary, optional components such as a conductive agent, a binder, a thickener, and a filler.
[0062] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ)O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.
[0063] The positive electrode active material is usually a particle (powder). The average particle diameter of the positive electrode active material is, for example, preferably 0.1 μm or more and 20 μm or less, more preferably 2 μm or more and 10 μm or less. By setting the average particle diameter of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle diameter of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle diameter of the composite is taken as the average particle diameter of the positive electrode active material. The "average particle diameter" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle diameter distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).
[0064] At least one of the positive electrode active material and the negative electrode active material described later contains hollow active material particles. The hollow active material particles are usually porous particles having through holes penetrating from the outer surface to the hollow portion, or continuous holes leading from the outer surface to the hollow portion. Examples of hollow positive electrode active material particles include secondary particles in which a plurality of primary particles of a positive electrode active material such as a lithium transition metal composite oxide are aggregated, and have a hollow portion formed inside. The hollow positive electrode active material particles can be publicly known hollow positive electrode active material particles described in Patent Documents 1 and 2, etc., and can be produced by a publicly known method described in Patent Documents 1 and 2, etc.
[0065] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.
[0066] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.
[0067] The content of the conductive agent in the positive electrode active material layer is preferably from 1 mass % to 10 mass %, and more preferably from 3 mass % to 9 mass %. By setting the content of the conductive agent in the above range, the energy density of the electricity storage element can be increased.
[0068] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0069] The content of the binder in the positive electrode active material layer is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 9% by mass, and even more preferably 3% by mass to 6% by mass. By setting the content of the binder in the above range, the positive electrode active material can be stably maintained.
[0070] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. When a thickener is used, the content of the thickener in the positive electrode active material layer can be 0.1% by mass or more and 8% by mass or less, and is usually preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain the thickener.
[0071] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When a filler is used, the content of the filler in the positive electrode active material layer can be 0.1% by mass or more and 8% by mass or less, and is usually preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain the filler.
[0072] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0073] (Negative electrode) As described above, the negative electrode 23 has a negative electrode substrate and a negative electrode active material layer laminated on both sides of the negative electrode substrate. The negative electrode may further have an intermediate layer provided between the negative electrode substrate and the negative electrode active material layer. It is also possible to use a negative electrode in which the negative electrode active material layer is laminated on only one side of the negative electrode substrate. The configuration of the intermediate layer that may be provided on the negative electrode is not particularly limited, and can be selected from the configurations exemplified for the positive electrode, for example.
[0074] The negative electrode substrate can be configured in the same manner as the positive electrode substrate, but the material is a metal such as copper, nickel, stainless steel, nickel-plated steel, or an alloy thereof, and copper or a copper alloy is preferred. The negative electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, or the like, and from the viewpoint of cost, a foil is preferred. Therefore, the negative electrode substrate is preferably a copper foil. Examples of the copper foil include rolled copper foil and electrolytic copper foil.
[0075] The negative electrode substrate may be a plate or sheet having a substantially uniform thickness. The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, even more preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be increased while increasing the energy density per volume of the energy storage element.
[0076] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, a filler, etc., as necessary. The optional components such as a conductive agent, a binder, a thickener, a filler, etc. can be selected from the materials exemplified for the positive electrode above.
[0077] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.
[0078] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO 2、 Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0079] "Graphite" refers to a material that has an average lattice spacing (d 002 ) is a carbon material with a particle size of 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite.
[0080] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.
[0081] Here, the "discharged state" of the carbon material means a state in which the carbon material, which is the negative electrode active material, is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material. For example, in a half cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode, the open circuit voltage is 0.7 V or more.
[0082] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.
[0083] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.
[0084] The negative electrode active material is usually in the form of particles (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be preferably 1 μm or more and 100 μm or less, more preferably 3 μm or more and 40 μm or less, and even more preferably 20 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be preferably 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the production or handling of the negative electrode active material becomes easy. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. Furthermore, when the negative electrode active material is a metal such as metallic Li, the form may be a foil.
[0085] As described above, at least one of the positive electrode active material and the negative electrode active material includes hollow active material particles. Examples of the hollow negative electrode active material particles include graphite particles having a hollow portion. As the hollow negative electrode active material particles, known hollow negative electrode active material particles described in the above Patent Document 2 and the like can be used, and can be produced by a known method described in the above Patent Document 2 and the like.
[0086] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass or more and 99% by mass or less, and more preferably 90% by mass or more and 98% by mass or less. By setting the content of the negative electrode active material in the above range, it is possible to achieve both high energy density and manufacturability of the negative electrode active material layer. When the negative electrode active material is metallic Li, the content of the negative electrode active material in the negative electrode active material layer may be 99% by mass or more, or may be 100% by mass.
[0087] (Separator) The separator 22 can be appropriately selected from known separators. For example, a separator consisting of only a base layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both sides of the base layer, etc. can be used as the separator. Examples of the shape of the base layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of electrolyte retention. As the material of the base layer of the separator, polyolefins such as polyethylene and polypropylene are preferable from the viewpoint of shutdown function, and polyimide and aramid are preferable from the viewpoint of oxidation decomposition resistance. A material in which these resins are combined may be used as the base layer of the separator.
[0088] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials that have a mass loss of a predetermined amount or less when heated include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.
[0089] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0090] As the separator, a polymer gel composed of a polymer and an electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.
[0091] (electrolyte) As the electrolyte, a non-aqueous electrolyte solution can be suitably used. The non-aqueous electrolyte solution includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.
[0092] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.
[0093] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.
[0094] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, DMC and EMC are preferred.
[0095] As the non-aqueous solvent, it is preferable to use at least one of a cyclic carbonate and a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When a cyclic carbonate and a chain carbonate are used in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.
[0096] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.
[0097] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0098] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less.3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.
[0099] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexyl, and the like. Aromatic compounds such as benzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, succinic anhydride, Glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, propane sultone, propene sultone, butane sultone, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2- dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, and the like.These additives may be used alone or in combination of two or more.
[0100] The content of the additive contained in the nonaqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or the charge / discharge cycle performance after high-temperature storage, and to further improve safety.
[0101] The electrolyte may contain water as a solvent.
[0102] <How to use the energy storage element> The energy storage element 10 can be used in the same manner as a conventionally known energy storage element. Moreover, the energy storage element 10 is used in a state in which the winding axis W of the electrode body 16 is arranged parallel to the horizontal direction.
[0103] That is, a method of using an energy storage element according to one embodiment of the present invention includes charging the energy storage element and discharging the energy storage element, the energy storage element including an electrode body formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in the longitudinal direction, an electrolyte, and a container for accommodating the electrode body and the electrolyte, at least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles, and the winding axis of the electrode body is parallel to the horizontal direction. The container is placed in a container, and at least the center of the electrode body is pressed due to the container being compressed. Excess electrolyte, which is a part of the electrolyte, is present between the electrode body and the container. The lower end of the electrode body is in contact with the excess electrolyte. When the height from the liquid level of the excess electrolyte to the upper end of the electrode body is H, the width of the positive electrode active material layer is Wc, the width of the negative electrode active material layer is Wa, and the width of the separator is Ws, at least one of the following formulas 1 to 3 is satisfied. 0.8H≦Wc≦2.0H 1 0.9H≦Wa≦2.1H 2 1.0H≦Ws≦2.2H 3
[0104] According to this usage method, even if charging and discharging are repeatedly performed, the resistance of the storage element is low and high output performance can be maintained. The specific form and preferred form of the storage element in this usage method are the same as those described for the storage element according to the embodiment of the present invention described above.
[0105] <Method of manufacturing the energy storage element> A method for producing an energy storage element according to one embodiment of the present invention includes housing an electrode assembly and an electrolyte in a container (housing step), and pressing the container (pressing step).
[0106] The electrode body is a wound type electrode body in which a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a strip-shaped negative electrode active material layer, and a strip-shaped separator are wound in the longitudinal direction. At least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles. In the housing step, the winding axis of the electrode body is arranged parallel to the horizontal direction. For example, when the bottom surface of the container is horizontal, the winding axis of the electrode body is arranged parallel to the bottom surface of the container.
[0107] The manufacturing method may include, for example, producing a wound flat electrode body and preparing an electrolyte solution before the accommodation step, etc. The manufacturing method may also include sealing the container between the accommodation step and the pressing step, etc.
[0108] The pressing step is performed by pressing the central portion of the wall surface 19 of the container body 17 from both side surfaces along the X-axis direction in the state of the energy storage element 10 in FIG. 1, for example, so that at least the central portion of the electrode body in the container is pressed. This pressing may cause the wall surface 19 of the container body 17 to deform so as to be recessed, as shown in FIGS. 1 and 4, and the deformed shape may be maintained as it is. Pressing may be performed by a conventionally known pressing member or the like. When the container body 17 (wall surface 19) is deformed by pressing using a pressing member, the pressing member may be removed as long as the deformed shape is maintained. In addition, for example, as in the case of an energy storage device described later, a pressing member may be used to hold the containers of the multiple energy storage elements in a pressed state so that they are fixed.
[0109] The manufacturing method may further include performing an initial charge / discharge. The initial charge / discharge may be a step of charging / discharging an uncharged / discharged energy storage element once or at least twice. The initial charge / discharge may be performed after the compression step or before the compression step.
[0110] In the energy storage element obtained through each of the above steps, at least the center of the electrode body is pressed, excess electrolyte, which is a part of the electrolyte, exists between the electrode body and the container, and the lower end of the electrode body is in contact with the excess electrolyte. When the height from the liquid level of the excess electrolyte to the upper end of the electrode body is H, the width of the positive electrode active material layer is Wc, the width of the negative electrode active material layer is Wa, and the width of the separator is Ws, at least one of the following formulas 1 to 3 is satisfied. 0.8H≦Wc≦2.0H 1 0.9H≦Wa≦2.1H 2 1.0H≦Ws≦2.2H 3
[0111] Specific and preferred aspects of the energy storage element obtained through the above-mentioned steps are similar to the specific and preferred aspects of the energy storage element described as one embodiment of the present invention.
[0112] In this production method, an electricity storage element that satisfies the above formula 1, 2 or 3 can be obtained by adjusting the amount of the electrolyte used, the size of the electrode body, and the like.
[0113] <Electricity storage device> The energy storage element of the present embodiment can be mounted as an energy storage device (battery module) configured by assembling a plurality of energy storage elements in a power source for an automobile such as an EV, HEV, or PHEV, a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, it is sufficient that the technology according to one embodiment of the present invention is applied to at least one energy storage element included in the energy storage device.
[0114] The energy storage device 40 shown in FIG. 7 has a plurality of energy storage elements 10. At least one of the plurality of energy storage elements 10 is the energy storage element (A), the energy storage element (B), or the energy storage element (C) according to one embodiment of the present invention. The plurality of energy storage elements 10 are arranged in a row via a spacer 41 and housed in a housing 42. The energy storage elements 10 are electrically connected to each other via a bus bar (not shown). In the energy storage device 40, the flat plate 44 presses each of the energy storage elements 10 via the spacer 41 as the nut 43 rotates. That is, in the energy storage device 40, the nut 43 and the flat plate 44 form a pressing member. The container of the energy storage element 10 is pressed (compressed) by such a pressing member, and at least the center of the electrode body in the container is pressed. The shape, size, material, and the like of the spacer 41 are appropriately set so that the electrode body in the container of each energy storage element 10 is sufficiently pressed. The specific structure of the energy storage element 10 provided in the energy storage device 40 is similar to that of the energy storage element 10 shown in FIG. 1 etc., and the winding axis of the electrode body is arranged parallel to the horizontal direction.
[0115] <Other embodiments> The present invention is not limited to the above-described embodiments, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0116] In the above embodiment, the case where the storage element is used as a chargeable and dischargeable secondary battery (e.g., a lithium ion secondary battery) has been described, but the type, size, capacity, number of components, etc. of the storage element are arbitrary. For example, the present invention can also be applied to a storage element having a plurality of electrode bodies in a container. In this case, it is sufficient that at least one electrode body satisfies the requirements of the present invention in terms of the relationship between the liquid level of the excess electrolyte and the electrode body. The storage element of the present invention can also be applied to capacitors such as electric double layer capacitors or lithium ion capacitors, storage elements using electrolytes other than non-aqueous electrolytes, etc. EXAMPLES
[0117] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0118] [Example 1] (Preparation of electrode body) Hollow positive electrode active material particles (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode mixture containing hollow secondary particles (O2, hollow secondary particles, area ratio 60%, average particle diameter 5 μm) was applied and dried to form a positive electrode active material layer. The width Wc of the positive electrode active material layer was 90 mm, and the average thickness Tc of the positive electrode active material layer (average thickness of the positive electrode - average thickness of the positive electrode base material) was 0.06 mm. In this way, a strip-shaped positive electrode was obtained. The area ratio and average particle diameter of the hollow positive electrode active material particles were values measured by the above-mentioned method. The same applies to the other active material particles described below. A negative electrode mixture containing hollow negative electrode active material particles (spheroidized natural graphite, hollow secondary particles, area ratio 80%, average particle diameter 8 μm) was applied to both sides of a belt-shaped copper foil negative electrode substrate so as to provide a non-laminated portion of the negative electrode active material layer, and then dried to form a negative electrode active material layer. The width Wa of the negative electrode active material layer was 95 mm, and the average thickness Ta of the negative electrode active material layer (average thickness of the negative electrode - average thickness of the negative electrode substrate) was 0.08 mm. This resulted in a belt-shaped negative electrode. A strip-shaped separator made of a microporous polyethylene film having a width Ws of 100 mm and an average thickness Ts of 0.02 mm was prepared. The strip-shaped positive electrode and the strip-shaped negative electrode were stacked together with the strip-shaped separator interposed therebetween, and the stack was then wound in the longitudinal direction to prepare a flat electrode body. A 1.2 mol / dm 3 LiPF6 was dissolved at a salt concentration of 100 to obtain a non-aqueous electrolyte. The electrode body was housed in an aluminum rectangular container, and a positive electrode terminal and a negative electrode terminal were attached. The nonaqueous electrolyte was poured into the container, which was then sealed. Next, the walls of the container were pressed from both sides to deform the electrode body in the container, so that at least the center of the electrode body in the container was pressed, thereby obtaining an electric storage element in which the electrode body was pressed. The following initial charge and discharge were carried out on the obtained uncharged storage element. At 25°C, constant current and constant voltage charging was carried out with a charging current of 0.2C and a charge cut-off voltage of 4.1V. The charge was terminated until the total charge time reached 3 hours. After a rest period of 10 minutes, constant current discharge was carried out with a discharge current of 0.2C and a discharge cut-off voltage of 2.5V, followed by a rest period of 10 minutes. In each of the examples and comparative examples, this charge and discharge was carried out for two cycles. After the initial charge and discharge, the energy storage element was left for 1 hour. After the energy storage element of Example 1 was left for 1 hour, the height H1 from the bottom of the container to the top of the electrode body and the height H2 from the bottom of the container to the liquid level of the excess electrolyte were measured by X-ray CT (computed tomography), and the height H (H1-H2) from the liquid level of the excess electrolyte to the top of the electrode body was calculated. The height H1 was 60 mm, the height H2 was 10 mm, and the height H was 50 mm.
[0119] [Examples 2 to 18, Comparative Examples 1 to 7] The energy storage elements of Examples 2 to 18 and Comparative Examples 1 to 7 were obtained in the same manner as in Example 1, except that the type (hollow or solid) of the positive electrode active material particles and negative electrode active material particles used, the height H1, the height H2, the width Wc of the positive electrode active material layer, the width Wa of the negative electrode active material layer, the width Ws of the separator, the average thickness Tc of the positive electrode active material layer (average thickness of the positive electrode - average thickness of the positive electrode base material), and the average thickness Ta of the negative electrode active material layer (average thickness of the negative electrode - average thickness of the negative electrode base material) were as shown in Table 1. The solid positive electrode active material particles are LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Single particles of O2 (primary particles, area ratio 98%, average particle diameter 5 μm) were used. In addition, crushed particles of bulk mesophase artificial graphite (area ratio 98%, average particle diameter 8 μm) were used as solid negative electrode active material particles.
[0120] [evaluation] (Charge-discharge cycle test) The following charge-discharge cycle test was carried out on each of the energy storage elements of the Examples and Comparative Examples after the initial charge-discharge. At 25° C., constant current charging was carried out with a charge current of 10 C and a charge cut-off voltage of 4.1 V. Thereafter, constant current discharging was carried out with a discharge current of 10 C and a discharge cut-off voltage of 2.5 V. In each of the Examples and Comparative Examples, this charge-discharge cycle was carried out 100 times. Each storage element before and immediately after the "charge-discharge cycle test" was charged at a constant current of 1C at 25°C to bring the SOC (State of Charge) to 50%, and then discharged at currents of 0.2C, 0.5C, and 1.0C in that order for 30 seconds each at 25°C. The relationship between the current at each discharge current and the voltage 10 seconds after the start of discharge was plotted, and the resistance (DC resistance) was calculated from the slope of the straight line obtained by plotting the three points. The resistances of the storage elements before and immediately after the charge-discharge cycle test are shown in Table 1 as relative values with the resistance of the storage element of Example 1 as the reference (100).
[0121] [Table 1]
[0122] As shown in Table 1, the energy storage elements of each Example in which hollow active material particles are used for the positive electrode active material or negative electrode active material and the relationship between the height H from the liquid level of the excess electrolyte to the upper end of the electrode body and the width Wc of the positive electrode active material layer, the width Wa of the negative electrode active material layer, or the width Ws of the separator is within a predetermined range has a resistance (relative value) of 120 or less after the charge-discharge cycle test, which shows that the resistance is low. Furthermore, a comparison of the energy storage elements of Examples 10 to 16 shows that the resistance after the charge-discharge cycle test is lower when the relationship between the sum of the average thickness Tc of the positive electrode active material layer, the average thickness Ta of the negative electrode active material layer, and the average thickness Ts of the separator and the height H from the liquid level of the excess electrolyte to the upper end of the electrode body is within a predetermined range. [Industrial Applicability]
[0123] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for automobiles, other vehicles, electronic devices, and the like. [Explanation of symbols]
[0124] 10 Energy storage element 11 Container 12 Positive terminal 13 Negative terminal 14 Positive electrode current collector 15 Negative electrode current collector 16 Electrode body 16A Curved section 17 Container body 18 Lid 19 Wall 21 Positive electrode 22(22a, 22b) Separator 23 Negative electrode 25 Positive electrode substrate 26 Cathode active material layer 27 Negative electrode substrate 28 Negative electrode active material layer 29 Positive electrode active material layer non-laminated portion 30 Negative electrode active material layer non-laminated portion 31 Excess electrolyte 40 Energy storage device 41 Spacer 42 Case 43 Nut 44 Flat plate
Claims
1. an electrode assembly formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in a longitudinal direction; Electrolyte, and A container for accommodating the electrode assembly and the electrolyte Equipped with At least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles, The winding axis of the electrode body is arranged parallel to the horizontal direction, The container is compressed, so that at least the center of the electrode body is pressed, Between the electrode body and the container, there is a surplus electrolyte which is a part of the electrolyte, The lower end of the electrode body is in contact with the excess electrolyte, The relationship between a height H from the liquid level of the excess electrolyte to the upper end of the electrode body and a width Wc of the positive electrode active material layer satisfies the following formula 1: 0.8H≦Wc≦2.0H...1
2. an electrode assembly formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in a longitudinal direction; Electrolyte, and A container for accommodating the electrode assembly and the electrolyte Equipped with At least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles, The winding axis of the electrode body is arranged parallel to the horizontal direction, The container is compressed, so that at least the center of the electrode body is pressed, Between the electrode body and the container, there is a surplus electrolyte which is a part of the electrolyte, The lower end of the electrode body is in contact with the excess electrolyte, The relationship between a height H from the liquid level of the excess electrolyte to the upper end of the electrode body and a width Wa of the negative electrode active material layer satisfies the following formula 2: 0.9H≦Wa≦2.1H...2
3. an electrode assembly formed by winding a strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a negative electrode active material layer, and a strip-shaped separator in a longitudinal direction; Electrolyte, and A container for accommodating the electrode assembly and the electrolyte Equipped with At least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles, The winding axis of the electrode body is arranged parallel to the horizontal direction, The container is compressed, so that at least the center of the electrode body is pressed, Between the electrode body and the container, there is a surplus electrolyte which is a part of the electrolyte, The lower end of the electrode body is in contact with the excess electrolyte, A storage element in which the relationship between a height H from the liquid level of the excess electrolyte to the upper end of the electrode body and a width Ws of the separator satisfies the following formula 3. 1.0H≦Ws≦2.2H...3
4. 4. The energy storage element according to claim 1, wherein the relationship between the average thickness Tc of the positive electrode active material layer, the average thickness Ta of the negative electrode active material layer, and the average thickness Ts of the separator and the height H satisfies the following formula 4: 1.0H≦500(Tc+Ta+Ts)≦2.0H...4
5. A strip-shaped positive electrode having a positive electrode active material layer, a strip-shaped negative electrode having a strip-shaped negative electrode active material layer, and a strip-shaped separator are wound in the longitudinal direction to form an electrode body, and an electrolyte is placed in a container; and Compressing the container Equipped with At least one of the positive electrode active material layer and the negative electrode active material layer has hollow active material particles, In the above-mentioned housing, the winding axis of the electrode body is arranged parallel to the horizontal direction, By applying the above pressure, At least the center of the electrode body is pressed, Between the electrode body and the container, there is a surplus electrolyte which is a part of the electrolyte, The lower end of the electrode body is in contact with the excess electrolyte, A method for manufacturing an energy storage element, wherein at least one of the following formulas 1 to 3 is satisfied, where H is a height from a liquid level of the excess electrolyte to an upper end of the electrode body, Wc is a width of the positive electrode active material layer, Wa is a width of the negative electrode active material layer, and Ws is a width of the separator. 0.8H≦Wc≦2.0H...1 0.9H≦Wa≦2.1H...2 1.0H≦Ws≦2.2H...3
6. One or more storage elements are provided, 5. An energy storage device, wherein at least one of the one or more energy storage elements is the energy storage element according to claim 1.
Citation Information
Patent Citations
Secondary battery using lithium
JP1996321300A
Battery case, nonaqueous electrolyte secondary battery equipped with battery case, and manufacturing method of nonaqueous electrolyte secondary battery
JP2008130371A
Active material particles, and use of same
JP2011119092A
Power storage element
JP2012209252A
Nonaqueous secondary battery
JP2013109929A